The complete chloroplast genome of a medicinal plant Epimedium koreanum Nakai (Berberidaceae). (1st November 2016) - Lee, Jung-Hoon; Kim, Kyunghee; Kim, Na-Rae; Lee, Sang-Choon; Yang, Tae-Jin; Kim, Young-Dong
Abstract: Epimedium koreanum is a perennial medicinal plant distributed in Eastern Asia. The complete chloroplast genome sequences of E. koreanum was obtained by de novo assembly using whole genome next-generation sequences. The chloroplast genome of E. koreanum was 157 218 bp in length and separated into four distinct regions such as large single copy region (89 600 bp), small single copy region (17 222 bp) and a pair of inverted repeat regions (25 198 bp). The genome contained a total of 112 genes including 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis with the reported chloroplast genomes revealed that E. koreanum is most closely related to Berberis bealei, a traditional medicinal plant in the Berberidaceae family.